Hematological of Jambal Siam Fish (Pangasius hypopthalmus) in Kuok Village Cultivation Pond, Bangkinang District West Kampar Regency - Herianti Rambe; Morina Riauwaty; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstrack This research was conduted from February to March 2018 in Kuok Village, West Bangkinang District, Kampar Regency and laboratory of Parasites and fish Diseases, Faculty of Fisheries and Marine,Universitas of Riau. This study aims to determine the health status of fish seen from the total erythrocytes, total leukocytes, hematocrit values, and hemoglobin levels, to stres levels in the Cultivation pond of Kuok District. Kampar Regency. The method used in this research is the survey method in three diffrent locations, namely in the Kuok Village Cultivation pond one, two, and three ponds. The type of feed given is in the form of commercial pellets which are given adlibitum three times a day.Sampling was done three times with a span of 10 days, the number of fish examinet was 90, each measuring 8-12 cm, the fish obtained from the pond are then taken using syirenge 1 ml which has been moistened with 10% EDTA solution and then the blood is put into the eppendorf tube, then stored in a coollbox and taken to the parasite and fish disease Laboratory, to calculate the total erythroxy, total leukocytes, hematokcrit value, and hemoglobin level. Based on observations of hematological parameter of siam jambal fish (pangasius hyphothalmus) total first erythrocyte sampling cells, one pond, 216x 104 cells/ mm3, two ponds 224x 104 cells/mm3 and three ponds at 221x 104 cells / mm3. Then the hematocrit value in pool one is 16.00% pon two 16,06 % and pool three is 14,13. Hemoglobin level one pond is 8,46 g/dL, pool two 9,43 g/dL while the total pool leukocytes were 193x 105 cells/mm3 and two pools were 142x 105 cells / mm3 and three pouds were 138x 105 cells/mm3.Key Words: Hematologycal, Pangasius hyphothalmus, cageculature, pond.